2020
DOI: 10.3390/agronomy10010142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV Radiation and Salt Stress on the Accumulation of Economically Relevant Secondary Metabolites in Bell Pepper Plants

Abstract: The green biomass of horticultural plants contains valuable secondary metabolites (SM), which can potentially be extracted and sold. When exposed to stress, plants accumulate higher amounts of these SMs, making the extraction and commercialization even more attractive. We evaluated the potential for accumulating the flavones cynaroside and graveobioside A in leaves of two bell pepper cultivars (Mavras and Stayer) when exposed to salt stress (100 mM NaCl), UVA/B excitation (UVA 4–5 W/m2; UVB 10–14 W/m2 for 3 h … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 46 publications
3
20
1
Order By: Relevance
“…This acclimation response has been reported for many different plant species and is driven by UV-B, UV-A, PAR (Latouche et al, 2013;Nybakken et al, 2004;Pollastrini et al, 2011;Rechner et al, 2016;Wang et al, 2020). The adjustments in UV-absorbing compounds in okra began within one day and lasted for 3 days of UV exposure (Figure S1) as previously shown in other species (e.g., grapevine, lettuce, barley, kale, Arabidopsis, common privet) (Agati et al, 2011;Barnes et al, 2013Barnes et al, , 2015Ellenberger et al, 2020;Kolb et al, 2005;Neugart et al, 2014). In grapevine, it was further shown that plants transferred to outdoor environments can increase flavonoids 10-fold over the course of 10 days (Latouche et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…This acclimation response has been reported for many different plant species and is driven by UV-B, UV-A, PAR (Latouche et al, 2013;Nybakken et al, 2004;Pollastrini et al, 2011;Rechner et al, 2016;Wang et al, 2020). The adjustments in UV-absorbing compounds in okra began within one day and lasted for 3 days of UV exposure (Figure S1) as previously shown in other species (e.g., grapevine, lettuce, barley, kale, Arabidopsis, common privet) (Agati et al, 2011;Barnes et al, 2013Barnes et al, , 2015Ellenberger et al, 2020;Kolb et al, 2005;Neugart et al, 2014). In grapevine, it was further shown that plants transferred to outdoor environments can increase flavonoids 10-fold over the course of 10 days (Latouche et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…Cynaroside also reduces kidney damage caused by the chemotherapeutic drug cisplatin, which is used to treat cancer [45]. The production of cynaroside has been increased in in vitro culture of Capsicum annum (aka bell pepper plant) by elicitation of UVA/B light for a period of 16 days [30].…”
Section: Uv-a and Uv-bmentioning
confidence: 99%
“…In the case of mild stresses, pretreatment with drought or UV-B may enhance subsequent tolerance to the other stress treatment. Conversely, combined salt and UV-A + B stress resulted in slightly lower fresh and dry weight of bell pepper plants than either of the single stresses ( Ellenberger et al 2020 ), while in poplar DNA lesions due to UV-B radiation were reduced when plants were simultaneously salt stressed ( Ma et al 2016 ). However, no detailed transcript and metabolite analyses have been published under such conditions.…”
Section: Introductionmentioning
confidence: 99%